Challenging Recurrence of Pyogenic Granuloma: A Case Report and Review of Evolving Therapeutic Strategies - Anjali, Anjali; Tandon, Sapna; Sharma, Chhavi; Chauhan, Himanshu; Mehra, Hemant; Sahin, Ibtisam (Journal of Neonatal Surgery, 2025)
Background: Pyogenic granuloma is a common benign reactive lesion of the gingiva that may develop due to local irritants, trauma, or hormonal factors. Despite being non-neoplastic, it has a high recurrence rate, particularly when incompletely excised or inadequately managed. Case Presentation: A female patient reported with a chief complaint of pain and soft tissue overgrowth in the upper right anterior maxillary region. She had a prior history of similar gingival swelling in the same area, treated at a private clinic months earlier. Clinical examination revealed a pedunculated, erythematous lesion involving the interdental papilla between teeth 14 and 15. There was no relevant medical history, family history, or pregnancy. Radiographic evaluation (orthopantomogram) revealed no bone involvement. A provisional diagnosis of pyogenic granuloma was made. Hormonal profiling was also conducted and found to be normal. Surgical excision was performed under local anesthesia using infraorbital, nasopalatine, and greater palatine nerve blocks. A marginal incision was placed 1 mm from the gingival margin, and the lesion along with adjacent papilla was excised. Thorough curettage and root planing were performed in the 14–15 region, followed by irrigation with povidone-iodine and saline. A Coe-Pak periodontal dressing was placed. The patient was followed up at 2 days, 1 week, 2 weeks, 1 month, 3 months, and 5 months, with additional debridement and reinforcement of oral hygiene. Healing progressed uneventfully. Conclusion: At 1-year follow-up, the surgical site showed complete healing with no signs of recurrence. Proper surgical technique, elimination of local irritants, and diligent follow-up were key to successful long-term management in this case of recurrent pyogenic granuloma.